POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN ANAK BERDASARKAN GENDER - Siti Rabiatul Adawiyah (Pusat Studi Gender dan Anak, IAIN Palu, 2021)
Children need education to increase their roles in society. Children education through formal, non-formal, and/or informal education is held to improve the quality of children's skills. Given the huge and importance of the process of parenting education, hence this study aims to determine the influence of parenting on children. Children are great blessings people must be grateful for, hence they deserve the best parenting by their parents. However, parents still treat their children differently. This discussion aims to identify various styles or methods of parenting and their impacts on children. This discussion consisted of four types of parenting proposed by Eisenburg et al. These parenting types are more specific and focused on children’s gender development than other parenting styles that are more general. The four types of parenting are channeling/shaping, direct introduction, differential treatment, and models. There are four types of parenting model according to some psychologists, which are authoritative parenting, neglectful parenting, permissive parenting, and democratic parenting. These four types have their own impacts. While some other opinions believe that authoritative parenting style has 6 (six) parenting styles, which are: Accept children's opinion, Ask about children's mistakes without accusing them, Give advice upon their mistakes, Give appreciation, Give presents, and Facilitate their hobbies.